Sub-site preferences of the aspartic proteinase from the human immunodeficiency virus, HIV-1 - Konvalinka, J; Strop, P; Velek, J; Cerna, V; Kostka, V; Phylip, L H; Richards, A D; Dunn, B M; Kay, J (FEBS letters, 1990)
A series of synthetic, chromogenic substrates for HIV-1 proteinase with the general structure Ala-Thr-His-Xaa-Yaa-Zaa*Nph-Val-Arg-Lys-Ala was synthesised with a variety of residues introduced into the Xaa, Yaa and Zaa positions. Kinetics parameters for hydrolysis of each peptide by HIV-1 proteinase at pH 4.7, 37 degrees C and u = 1.0 M were measured spectrophotometrically and/or by reverse phase FPLC. A variety of residues was found to be acceptable in the P3 position whilst hydrophobic/aromatic residues were preferable in P1. The nature of the residue occupying the P2 position had a strong influence on kcat (with little effect on Km); beta-branched residues Val or Ile in this position resulted in considerably faster peptide hydrolysis than when e.g. the Leu-containing analogue was present in P2.
Keywords: molekulární sekvence - údaje; HIV Protease; Amino Acid Sequence; Gene Products, pol; endopeptidasy; Endopeptidases; Kinetics; genové produkty pol; HIV-1; Substrate Specificity; HIV-proteasa; substrátová specifita; kinetika; sekvence aminokyselin; Molecular Sequence Data